Formulasi sediaan patch dari ekstrak etanol daun laban (Vitex pinnata L.) sebagai antiinflamasi - Rahmi , Ulfa; Dalimunthe, Gabena Indrayani; Yuniarti , Rafita; Rani , Zulmai (Journal of Pharmaceutical and Sciences, 2025)
Laban leaves (Vitex pinnata L.) contain flavonoids, saponins, tannins, and steroids, which have anti-inflammatory potential. This research aims to formulate laban leaves into an anti-inflammatory patch preparation for the back skin of mice induced by 3% carrageenan. Laban leaf simplicia was extracted using the maceration method using 96% ethanol, and patch preparations were made with varying extract concentrations of 5, 7.5, and 10%. The patch preparation is tested organoleptic, pH, weight uniformity, patch thickness, patch moisture, patch crease resistance, and irritation. The anti-inflammatory activity of the patch preparation was analyzed using the inflammatory associate edema method, namely measuring the anti-inflammatory effect using a caliper and 25 test animals, which were divided into 5 groups, namely negative control, positive control, and treatment group with a concentration of 5; 7.5; and 10% with 5 individuals each. The results of several tests that have been carried out are analyzed using the one-way ANOVA program. The results show the anti-inflammatory activity of laban leaves. There was no difference in the percentage of edema inhibition data on the back skin of mice between treatment groups. This shows that the anti-inflammatory patch preparation of Laban leaf extract (Vitex pinnata L.) has anti-inflammatory activity. The formula that provides the most potent anti-inflammatory activity is a patch preparation with an extract concentration of 10%. With an edema inhibition percentage of 59%.